2016
DOI: 10.1007/s10661-016-5602-y
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate communities and the relationships with biotic factors in river-connected lakes in the lower reaches of Yangtze River, China

Abstract: The relationships of macroinvertebrate communities with abiotic factors in lake and river system were well documented, but their relationships with biotic factors were few explored. The macroinvertebrate communities in two river-disconnected lakes (Poyang Lake and Shijiu Lake) and the rivers connected to Shijiu Lake were investigated to reveal the differences in communities and explore the relationships with biotic factors. A total of 34 species were recorded in the three water bodies. Combined with the previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although it is an occasional species only sampled one time, the appearance of this species has very important ecological interest. Many studies showed the upper limit of distribution of this species only reached to the Poyang lake and its surrounding lakes located in the lower reaches of Yangtze river (Wang et al, 2007;Ouyang et al, 2009;Cai et al, 2013Cai et al, , 2014Chi et al, 2016). As an estuarine and marine species, the species Nephtys sp.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is an occasional species only sampled one time, the appearance of this species has very important ecological interest. Many studies showed the upper limit of distribution of this species only reached to the Poyang lake and its surrounding lakes located in the lower reaches of Yangtze river (Wang et al, 2007;Ouyang et al, 2009;Cai et al, 2013Cai et al, , 2014Chi et al, 2016). As an estuarine and marine species, the species Nephtys sp.…”
Section: Discussionmentioning
confidence: 99%
“…After the connection between the rivers and the lakes was reestablished, some changes in the characteristics of each lake environments occur (Casanova et al 2009 ). River connected lakes exhibit a high degree of biodiversity, leading to an enhanced biological diversity of aquatic ecosystems (Chi et al 2016 ).…”
Section: Hydrological Connectivity At Multiscales and Its Effects On Ecohydrologymentioning
confidence: 99%